Locomotive performance testing apparatus (2013)
Provided is a locomotive performance testing apparatus capable of testing the locomotive performance of a test subject while keeping the test subject at a suitable position on a treadmill. According to the locomotive performance testing apparatus, a robot is moving its legs toward a second direction on a plurality of endless belts which are rotationally driven by a plurality of motors, respectively. In this situation, a positional deviation or the like of the robot from a first desired position in a first direction different from a second direction is determined as a first deviation. Moreover, motions of the plurality of motors are individually controlled to offset the first deviation.